THE FIXED BAFFLE EFFECT ANALYSIS TO FILLING TANKS VARIATION ON THE STABILITY OF 4999 DWT TANKERS - Yudo, Hartono; Amiruddin, Wilma; Guna Satriananta, Mahendra; Putra Nur Hidayat, Wahyu (Marine & Earth Science and Technology Research Center, DRPM, ITS, 2021)
The tanker is transportation to distribute the results of oil and gas exploration, where most of the exploration results come from the ocean. In this study, an analysis of the effect of adding fixed baffles with a certain number of baffles on the stability of the tanker will be carried out. The method in this study is to analyze the data of 4999 DWT tankers using Maxsurf Stability Software. The simulation was carried out in 4 percentage variations, namely 30%, 40%, 70%, and 90%, with full baffle installation in each tank. After calculating the stability analysis on the 4999 DWT tanker, it was found that the model I tank (without baffles) did not meet IMO standards. While the model II tank (1 fixed baffle), model III tank (2 fixed baffles), and model IV tank (3 fixed baffles) on various fillings have met IMO standards. Where the tank model IV (3 fixed baffles) has the best stability value with a GZ value of 1.881 m at 30% filling, 1.602 m at 50% filling, 1.051 m at 70% filling, and 0.706 m at 90% filling. It was concluded that the addition of a fixed baffle to the tank was effective in increasing the stability of the tanker.